The great white hope [videorecording (DVD)] - Jones, James Earl; Alexander, Jane, 1939-; Ritt, Martin, 1914-1990; Sackler, Howard (Twentieth Century Fox Home Entertainment, 2004)
Fictional account of African American boxer of the early 1900s who defies social conventions by having an affair with a white women and who is attacked for his outspoken racial views.